"Przełom" - problem autorstwa poematu = "Przełom" [The Turn] - the problem of authorship - Kozłowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the poem "Przełom" [The Turn], one of three questionable poems stored in the Cracow Curia Archive. The paper deals with the overview of the editorial history of this text and the debate on its attribution. The main purpose of the article is to gather, formulate and evaluate arguments - both external and internal - on its autorship.
Keywords: Jan Paweł II, papież (1929-2005); poezja polska - 20 w.